Analysis of Development of Chicken Meatballs Using The Quality Function Deploment (QFD) Method (Study Case: Hasnia Chicken Meatballs Business in Tahandouna Village Poasia District Kendari City) - Arman, Arman; Rianda, La; Rosmawaty, Rosmawaty (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This study aims to (1) determine the process of processing chicken meatball products and (2) determine the process of developing chicken meatball products using the QFD (Quality Function Deployment) method in the Hasnia Chicken Meatball Business in Rahandouna Village, Poasia District, Kendari City. The determination of the sample is done by purposive sampling. The results showed that the process of producing chicken meatballs in the Hasnia Chicken Meatball business contained eight stages, which were in accordance with the literature. The eight stages were: raw material preparation, chicken cleaning, chicken meat crushing, dough making, dough forming, cooking, product cooling, and product packaging. Hasnia Chicken Meatball product development obtained 26 attributes, obtained 6 main priority attributes in fulfilling needs with the highest value of each type of attribute, (1) include the expiration date with a value of 16.28 (7.23%), (2) delicious aroma of chicken meatballs and appetizing with a value of 8.57 (3.81%), (3) chicken meatball products have a superior taste compared to other places with a value of 8.14 (3.61%), (4) chicken meatball products sold are superior to other products with a value of 7.71 (3.42) %), (5) the price of chicken meatballs corresponds to the price with a value of 7.33 (3.26%), (6) the texture attribute of the chicken meatballs is chewy with a value of 7.26 (3.22%).